Sandinista : Carlos Fonseca and the Nicaraguan revolution - Zimmermann, Matilde, 1943- (E-Duke books scholarly collection., 2000)
The life and ideas of Carlos Fonseca Amador, founder of the Sandinista National Liberation Front (FSLN).